30.2k views
21 votes
4x + 3 = x + 2(x + 7)
step by step

User Hestellezg
by
5.4k points

2 Answers

8 votes

Answer:

x=11

Explanation:

Distribute :

4x + 3 = x + 2( x+ 7)

4x + 3 = x + 2x + 14

Combine like terms :

4x + 3 = x + 2x + 14

4x + 3 = 3 x+ 14

Subtract 3 from both sides of the equation :

4x + 3 = 3x + 14

4x + 3-3 = 3x + 14 -3

Simplify :

what ever way you know how to subtract the numbers you should get this answer :

4x = 3x + 11

Subtract 3 from both sides of the equation :

4x = 3x + 11

4x - 3x = 3x + 11 - 3x

Simplify :

combine like terms

multiply by 1

combine like terms

x= 11

User Rajesh Pandya
by
5.5k points
10 votes

Answer:

x=11

Explanation:

4x + 3 = x+ 2x + 14

4x + 3 = 3 x + 14

4x - 3x = 14 -3

x= 14 - 3

x= 11

User Heiner
by
5.3k points